Zn:DLC films via PECVD-HIPIMS: Evaluation of antimicrobial activity and cytotoxicity to mammalian cells - De O. Correia, Rebeca F.B.; Sampaio, Aline G. [UNESP]; Milhan, Noala V.M. [UNESP]; Capote, Ariel; Gerdes, Holger; Lachmann, Kristina; Trava-Airoldi, Vladimir J.; Koga-Ito, Cristiane Yumi [UNESP]; Bandorf, Ralf (American Vacuum Society, 2023)
DLC films were grown with Zn via a combined plasma-enhanced chemical vapor deposition (PECVD) and high-power impulse magnetron sputtering (HIPIMS) process. The films were deposited on textiles in an atmosphere of Ar and C2H2, and the percentage of metal in the DLC was varied by controlling the acetylene gas flow. At first, to evaluate the antimicrobial activity, a screening test with the ISO 22196 standard was carried out. Afterward, AATCC TM100:2019 was used to evaluate the antimicrobial effectiveness of the films on textiles. The antimicrobial effectiveness of the coating was studied against a Gram-negative bacterium (Escherichia coli), a Gram-positive bacterium (Staphylococcus aureus), and a fungus (Candida albicans), after a 24 h contact. In addition, the cytotoxicity of the samples to mammalian cells was evaluated by indirect contact. For this, the samples were soaked into the growth media for 1 and 7 days, and then, the extracts were collected and put in contact with keratinocytes for 24 h. Finally, the properties of the films were also evaluated as a function of the Zn content, such as their structural quality, morphology, hardness, wear resistance, and coefficient of friction. The films showed excellent results against all microorganisms, with 100% effectiveness in some cases. The pure extracts obtained from all the samples with the incorporation of metals were cytotoxic. Despite that, the cell viability after contact with some Zn-DLC diluted extracts (10%) was not different from that observed in the uncoated group. Besides, increasing the Zn content resulted in a film with poorer mechanical properties but did not affect the coefficient of friction of the coating.